Transparent hemicellulose-DWCNT electrode - Pasanen, Hannu (2015)
Carbon nanotubes (CNTs) and graphene have shown promising potential as next-generation transparent conducting materials due to their high electrical and thermal conductance, flexibility and transparency in both visible and infrared spectral regions. In this study transparent and conductive thin films with a novel hemicellulose and double-walled carbon nanotube (HC-DWCNT) hybrid material were produced with spray-coating, droplet casting and vacuum filtration deposition methods. HC-DWCNT material is easily dispersed in water and usable for mass-production. These films showed good conductivity, stability at ambient air, very good transparency in the visible and excellent transparency in the infrared spectral regions while having few percent haze. The best sample had sheet resistance of 115 ± 9 ohm/sq and direct transmittance of 81.6 % at 550 nm wavelength. The properties of the prepared films were compared to CNT, graphene and their hybrid films reported by research groups by reviewing their fabrication methods and film performances. While many of these other films have shown higher shortterm quality, it was found that the performances of HC-DWCNT films were quite promising for future development considering the stability of the films and the fact that dopants or post-treatments were not used for enhancing the performance of the best samples.